Modulating the oxidative active species by regulating the valence of palladium cocatalyst in photocatalytic degradation of ciprofloxacin - Guo, Fa; Zhang, Hao; Li, Hui; Shen, Zhurui (Applied catalysis. B, Environmental, 2022)
Nano-structured metal cocatalysts are easy to be oxidized and form mixed valences and interfaces which would facilitate the catalytic performance in previous studies. Herein, as an example in photocatalysis, three kinds of Pd cocatalysts with various valence distributions (PdO70-Pd30/CN, PdO50-Pd50/CN and PdO30-Pd70/CN) were loaded on g-C3N4 nanosheets with the close loading amounts (~1 wt%) and uniform sizes (2–3 nm). Then, the results of the photocatalytic degradation of ciprofloxacin showed that the generated oxidative active species are highly related to the distribution of palladium valence. Pd2+ (PdO) benefits the production of·O2-, while Pd0 benefits the production of h+. The theoretical simulations revealed that surface states e.g., electron distribution and the adsorption ability of O2 on different Pd species determined the production of·O2- and h+. Besides, PdO50-Pd50/CN showed the best performance for degrading ciprofloxacin, due to the joint action of·O2- and h+ in the CIP degradation. [Display omitted] •The correlation is studied between the valence of Pd cocatalyst and active species in photocatalysis.•The distribution of active species is semi-quantitative correlated with the ratios of Pd2+/Pd0.•Amongst, Pd2+ (PdO) benefits the production of·O2-, while Pd0 benefits the production of h+.•The surface states of Pd are crucial, e.g., the adsorption ability of O2 and electrons distribution.•The nearly equal ratios of·O2- and h+ resulted in the best degradation efficiency of ciprofloxacin.